Hi guys, I've been stuck on this question for days!
If x= √3/2
Find the value of the expression
1+x/1+√(1+x) + 1-x/1-√(1-x)
Thanks!
following on from what u had....
(1+x)(1-√1-x)/)1+√1+x)(1-√1-x) + (1-x)(1+√1+x)/(1-√1-x)1+√1+x)
= (1+x)(1-√1-x) + (1-x)(1+√1+x)/1+√1+x)(1-√1-x)
=2-√1-x - x√1-x + √1+x -x1+x/(1+√1+x)(1-√1-x)
=2-√1-x(1+x) + √1+x(1-x)/(1+√1+x)(1-√1-x)
Thats as far as i could get :s
I don't think my suggestion will simplify it enough.
simplify ((1+(sqrt[3]/2) 1;/(1+sqrt[1+(sqrt[3&# 93;/2)]))+((1-(sqrt[3]/2))/(1-sqrt[1-(sqrt[3]/2)]